1997
DOI: 10.1152/ajpcell.1997.272.1.c254
|View full text |Cite
|
Sign up to set email alerts
|

Effects of F-actin stabilization or disassembly on epithelial Cl- secretion and Na-K-2Cl cotransport

Abstract: Previous studies showed that cAMP-dependent transepithelial Cl- secretion of the intestinal cell line T84 is reduced by the F-actin stabilizer phalloidin, an effect in part attributable to inhibition of basolateral Na-K-2Cl cotransport. However, secretory responses are preserved in cells treated with the microfilament disrupter cytochalasin D. We explored the effects of cytochalasin D and two novel compounds derived from marine sponges on the Cl- secretory apparatus of T84 cells. Jasplakinolide (which stabiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 27 publications
6
44
1
Order By: Relevance
“…Although apical membrane Cl Ϫ channels, and in particular CFTR, are generally held to be the primary regulatory site for epithelial Cl Ϫ secretion, it is clear that Cl Ϫ uptake across the basolateral membrane must also increase to balance apical Cl Ϫ exit and to preserve intracellular ion and volume homeostasis under changing physiologic demands. We have previously identified several conditions under which the regulation of the basolateral Na-K-2Cl cotransporter appears to limit the rate of transepithelial Cl Ϫ transport (17,18,47). Our findings with butyrate-treated T84 cells further supports this concept.…”
Section: Discussionsupporting
confidence: 80%
“…Although apical membrane Cl Ϫ channels, and in particular CFTR, are generally held to be the primary regulatory site for epithelial Cl Ϫ secretion, it is clear that Cl Ϫ uptake across the basolateral membrane must also increase to balance apical Cl Ϫ exit and to preserve intracellular ion and volume homeostasis under changing physiologic demands. We have previously identified several conditions under which the regulation of the basolateral Na-K-2Cl cotransporter appears to limit the rate of transepithelial Cl Ϫ transport (17,18,47). Our findings with butyrate-treated T84 cells further supports this concept.…”
Section: Discussionsupporting
confidence: 80%
“…For instance, patch clamp analysis revealed that phalloidin can inhibit K ϩ and Na ϩ channels (32,33). Similarly, jasplakinolide prevents the activation of Cl Ϫ secretion induced by cAMP (34), which is believed to be mediated by a conductive pathway. Cytochalasins have been found to stimulate Na…”
Section: Actin Cytoskeleton and Namentioning
confidence: 99%
“…To elucidate whether the actin cytoskeleton was involved in cytochalasin B-induced inhibition of hKv1.5 channels, we further examined the effects of other actin disruptors, such as cytochalasin D and cytochalasin J and an actin filament stabilizer phalloidin (22,35) on the cytochalasin B-induced inhibition of hKv1.5 (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%